Peningkatan Kemampuan Menggosok Gigi melalui Media Gambar Sequence pada Anak Disabilitas Grahita Sedang Kelas II - Sakinah, Nurul; Yaum, Lailil Aflahkul; Sukmawati, Bhennita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the improvement of tooth brushing skills through picture sequences among students with intellectual disabilities at Batang State Special Needs School (SLB Negeri Batang). This study employed Kemmis' 3-classroom action research model, utilizing two cycles. The results showed that in Cycle I, the average skill achievement was still below 60%, with low participation. Cycle II showed improvement through the use of interactive picture sequences, with an average skill score above 80%. In Cycle III, most students were able to perform all tooth brushing steps independently without assistance, with achievement rates ranging from 91.6 to 100%. This study concludes that the use of picture sequences is efficacious in improving self-help toothbrushing skills in children with moderate intellectual disabilities at Batang State Special Needs School (SLB Negeri Batang). Keywords: Picture Sequence, Moderate Intellectual Disability, Tooth Brushing